ANALYSIS OF CHALLENGES IN INTER-REGIONAL COLLABORATION IN THE MANAGEMENT OF BUS TRANS JATIM BUSES - Prasada, Yasinta Aulia Bilqis; Esyi, Almardlina Jantika; Deswita, Shafira Ayu (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
Trans Jatim Buses is a public transportation system developed by the East Java Provincial Government to improve connectivity between regions and reduce traffic congestion in the Gerbangkertosusilo agglomeration area. However, in its implementation, the management of Trans Jatim Bus faces various collaborative challenges between regions. Differences in regulations, fiscal capacity, and sectoral interests in each region are factors that hinder the effectiveness of this service. This study aims to identify the main challenges in inter-regional coordination and examine the factors that support and hinder the success of collaboration in the management of Bus Trans Jatim. The method employed is a literature review, analyzing the Collaborative Advantage and Collaborative Inertia theories proposed by Huxham and Vangen (2005). The results of the study indicate that inter-regional collaboration in managing the East Java Bus Service remains suboptimal due to differences in objectives, unequal participation, weak institutional coordination, and power dynamics. Therefore, a more structured cooperation mechanism is needed from the provincial government and the establishment of binding regulations as a legal framework for more participatory inter-regional cooperation that is oriented towards common goals.